2008
DOI: 10.1093/jac/dkn309
|View full text |Cite
|
Sign up to set email alerts
|

Switch from zidovudine- to non-zidovudine-containing regimens is associated with modest haematological improvement and no obvious clinical benefit: a substudy of the ANRS 099 ALIZE trial

Abstract: Background: Zidovudine, the first antiretroviral agent, has short-term haematological toxicity. However, it is unclear whether patients tolerating long-term zidovudine-containing regimens will benefit from a switch to non-zidovudine-containing regimens.Methods: One hundred and fifty-eight patients enrolled in the ALIZE trial receiving zidovudine at baseline were analysed. These patients were randomized to continue their regimen or to switch to a combination of emtricitabine, didanosine and efavirenz for 48 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The Simplification With Easier Emtricitabine and Tenofovir (SWEET) study demonstrated reduced incidence of anemia and improved lipid parameters after switching from ZDV/3TC to TDF/FTC 54 . Other studies have also demonstrated similar results 55,56 . Preliminary evidence from Thailand suggests that treatment-limiting toxicity associated with ZDV can be reduced without compromising efficacy if administered at the reduced dose of 200 mg twice daily 57 .…”
Section: 0 Efficacy and Safety Of Combination N(t)rtissupporting
confidence: 74%
“…The Simplification With Easier Emtricitabine and Tenofovir (SWEET) study demonstrated reduced incidence of anemia and improved lipid parameters after switching from ZDV/3TC to TDF/FTC 54 . Other studies have also demonstrated similar results 55,56 . Preliminary evidence from Thailand suggests that treatment-limiting toxicity associated with ZDV can be reduced without compromising efficacy if administered at the reduced dose of 200 mg twice daily 57 .…”
Section: 0 Efficacy and Safety Of Combination N(t)rtissupporting
confidence: 74%
“…Of all MOS-HIV domains measured, only one significant difference between groups was observed; compared to CPI/r, TPV/r was associated with a small but significant improvement in pain scores (+4.8 points; P <0.05). A study by Lafaurie et al (2008) [15] evaluated HIV-infected adults receiving a PI-containing ARV regimen and compared maintenance of the current PI-containing regimen versus switch to a once-daily NNRTI-based regimen of EFV/ddI/emtricitabine (FTC). Although a medium effect was observed in the PHS score in the switch arm (mean change −1.76, effect size 0.53), the difference in change from baseline to 48 weeks in both PHS and MHS scores was not statistically significant between treatment groups ( P =0.57 and P =0.42, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Switch from zidovudine was associated with significant improvements in hemoglobin level and neutrophil counts parameters. 42 Also, switch from a thymidine analog to TDF leads to significant improvement in limb fat mass, metabolic parameters, and mitochondrial toxicity. 43 46 …”
Section: Discussionmentioning
confidence: 99%